Captain America. Vol. 3, Broxton rising - Straczynski, J. Michael, 1954- (Marvel Worldwide, Inc., 2025)
As the Krakoan age ends, mutants need allies more than ever - and Captain America is determined to get his group of mutant change agents to the Front Door Cabaret alive. As Death pulls out all the stops to destroy them, Captain America has a choice: protect the change agents or safeguard his own future. But one of the rescued mutants has their own ideas and intends to make the decision for him!--